The scope of mental health research during the COVID-19 pandemic and its aftermath - Hotopf, Matthew (Br J Psychiatry, 2020)
The effects of the COVID-19 pandemic on population mental health are unknown. We need to understand the scale of any such impact in different sections of the population, who is most affected and how best to mitigate, prevent and treat any excess morbidity. We propose a coordinated and interdisciplinary mental health science response.